Research on Doctor-patient Emotional Interaction on Online Medical Consultation Platforms - Jiaqi LI; Hongmei OU (Yixue yu zhexue)
Based on discourse analysis theory, by analyzing the conversational corpus on Chunyu Doctor website, this study distinguishes different types of patients' emotional expression and doctors' response in online medical communication. The findings reveal that patients tended to express negative emotions directly first, and then indirectly. Doctors, on the other hand, focus on completing medical tasks first, often delaying emotional responses. Additionally, patients have cognitive biases in obtaining medical information, resulting in emotional fluctuations that prevent doctors from responding emotionally before first correcting misunderstandings. In addition, the themes of doctor-patient emotional interaction are diverse, including not only negative emotions related to illness, but also practical issues such as delayed response apologies, financial concerns, and medical resource limitations. With the development of online medical consultation, the importance of doctor-patient emotional interaction has become more and more prominent, which is of great significance to both doctors and patients.